2017
DOI: 10.1155/2017/9671604
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils and Immunity: From Bactericidal Action to Being Conquered

Abstract: The neutrophil is the major phagocyte and the final effector cell of the innate immunity, with a primary role in the clearance of extracellular pathogens. Using the broad array of cytokines, extracellular traps, and effector molecules as the humoral arm, neutrophils play a crucial role in the host defense against pathogen infections. On the other hand, the pathogen has the capacity to overcome neutrophil-mediated host defense to establish infection causing human disease. Pathogens, such as S. aureus, have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
136
0
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 135 publications
0
136
0
13
Order By: Relevance
“…Neutrophils, one of the major cell populations of innate-immune system play a pivotal role in host defense against pathogens [34]. Depletion of neutrophils frequently leads to a fatal complication, while excessive activation of neutrophils results in host tissue damage [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils, one of the major cell populations of innate-immune system play a pivotal role in host defense against pathogens [34]. Depletion of neutrophils frequently leads to a fatal complication, while excessive activation of neutrophils results in host tissue damage [35].…”
Section: Discussionmentioning
confidence: 99%
“…10 Neutrophils, one of the major cell populations of innate-immune system play a pivotal role in host defense against pathogens. 34 Depletion of neutrophils frequently leads to a fatal complication, whereas excessive activation of neutrophils results in host tissue damage. 35 The protective and harmful effects of neutrophils depend on the stages of sepsis, as at the onset of sepsis neutrophils are important in attenuating bacteremia, whereas at the late onset of sepsis prolonged and excessive infiltration of neutrophils often causes organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are a crucial effector cell, are the main phagocytes of the innate immune system and play an important role in clearing pathogenic micro-organisms (38). Izumi et al (39) found significantly impaired neutrophil chemotaxis and periodontal disease in adults with DS vs. healthy controls (n = 14 in both groups) which they suggested may have a role in the poorer oral health of this population.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Neutrophils defend the host against pathogen infection via phagocytosis, degranulation, and generation of neutrophil extracellular traps and the release of a variety of effector molecules (193). In neutrophils, addition of soluble CCL2 induced the activation of PI3K/Akt, ERK, and NF-κB in vitro, which led to a decrease in constitutive apoptosis in these cells.…”
Section: Ccl2 Enhances Myeloid Cell Survival and Proliferationmentioning
confidence: 99%